Composite prepreg and fiber reinforced resin molding

The composite prepreg with a thermoplastic and thermosetting resin layer, featuring continuous reinforcing fibers, addresses manufacturing challenges by ensuring strong bonding and improved mechanical properties for complex shape fabrication.

JP7619044B2Active Publication Date: 2025-01-22TORAY INDUSTRIES INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020564951
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-23
Filing Date
2020-11-12
Publication Date
2025-01-22
Estimated Expiration
2040-11-12

AI Technical Summary

Technical Problem

Existing fiber-reinforced composite materials face challenges in manufacturing complex shapes due to unsuitable joining methods for thermosetting and thermoplastic resins, leading to increased manufacturing time and reduced mechanical properties.

Method used

A composite prepreg is developed with a thermoplastic resin layer containing continuous reinforcing fibers and a thermosetting resin layer, bonded through an interface, ensuring high adhesive strength and secondary weldability, with reinforcing fibers distributed across 80% of the layer thickness, enhancing mechanical properties and handling.

Benefits of technology

The composite prepreg exhibits excellent mechanical properties, reduced warping, and improved handling, with tight bonding between layers, allowing for efficient manufacturing of complex shapes without layer separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619044000003
    Figure 0007619044000003
  • Figure 0007619044000004
    Figure 0007619044000004
  • Figure 0007619044000005
    Figure 0007619044000005
Patent Text Reader

Abstract

To attain an objective of providing a prepreg and a fiber-reinforced resin molded product that excel in secondary weldability with other members and exhibit excellent handleability and reinforcing properties, there is provided a prepreg including a thermoplastic resin layer and a thermosetting resin layer in which a thermoplastic resin and a thermosetting resin are impregnated in reinforcing fibers and which are joined to each other by forming an interface, wherein the thermoplastic resin layer is present on at least one surface, the thermoplastic resin layer includes continuous reinforcing fibers, the reinforcing fibers are distributed in a region of 80% or more of the thickness of each layer of the thermoplastic resin layer and the thermosetting resin layer in a cross section perpendicular to the plane direction, and an adhesive strength between the thermoplastic resin layer and the thermosetting resin layer is 1 N / 24 mm or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite prepreg formed by combining a thermoplastic resin layer and a thermosetting resin layer, and a fiber-reinforced resin molding obtained from the prepreg. [Background technology]

[0002] Fiber-reinforced composite materials, which use thermosetting or thermoplastic resins as a matrix and combine them with reinforcing fibers such as carbon fiber and glass fiber, are lightweight yet have excellent mechanical properties such as strength and rigidity, as well as heat resistance and corrosion resistance, and have therefore been applied to many fields, including aerospace, automobiles, railway vehicles, ships, civil engineering and construction, and sporting goods.

[0003] However, fiber-reinforced composite materials using thermosetting resins are not suitable for producing parts or structures having complex shapes in a single molding process, and for the above-mentioned applications, it is necessary to prepare a component made of a fiber-reinforced composite material and then integrate it with a component of the same or a different type.

[0004] Conventionally, methods for integrating the same or different types of components with fiber-reinforced composite materials using thermosetting resins have generally been mechanical joining methods using bolts, rivets, screws, etc., or joining methods using adhesives. Mechanical joining methods require a step of pre-processing the joining parts, such as drilling holes, which leads to a long manufacturing process and increased manufacturing costs, and there is also the problem that the material strength decreases due to the need to drill holes. Joining methods using adhesives require a bonding process and a curing process, including preparation and application of the adhesive, which leads to a long manufacturing process, and there is also the problem that the reliability of the adhesive strength is not fully satisfactory.

[0005] Fiber-reinforced composite materials using a thermoplastic resin as a matrix can be used to join components by welding, in addition to the above-mentioned mechanical joining methods and joining using adhesives, so there is a possibility that the time required for joining components can be shortened. However, when mechanical properties at high temperatures and excellent resistance to chemicals are required, such as in aircraft structural components, there is an issue that the heat resistance and chemical resistance are insufficient compared to fiber-reinforced composite materials made of thermosetting resins and reinforcing fibers.

[0006] Here, Patent Document 1 discloses a method for integrating a member made of a thermoplastic resin with a member made of a fiber-reinforced composite material made of a thermosetting resin. That is, in the method described in this document, a thermoplastic resin film is laminated on the surface of a prepreg sheet made of reinforcing fibers and a thermosetting resin, and a fiber-reinforced composite material is obtained by heating and pressing. The obtained fiber-reinforced composite material is then placed in a mold, and a thermoplastic resin is injection-molded to bond the thermoplastic resin member formed by injection molding to the fiber-reinforced composite material.

[0007] Patent Document 2 describes a discontinuous fiber reinforced resin sheet, one surface of which is impregnated with a thermoplastic resin and the other surface of which is impregnated with an adhesive resin.

[0008] Patent Document 3 describes that a fiber-reinforced composite material is obtained by disposing a thermoplastic resin on the surface of a reinforcing fiber substrate, and then injecting and curing a thermosetting resin at the same time or after the thermoplastic resin is disposed on the surface of the reinforcing fiber substrate. Such a fiber-reinforced composite material allows other members to be welded to the surface of the thermoplastic resin.

[0009] Patent Document 4 describes a prepreg that contains a thermoplastic resin in a range from the surface to a depth of 20% of the thickness. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Japanese Patent Application Publication No. 10-138354 [Patent Document 2] International Publication No. 2014 / 103658 Brochure [Patent Document 3] JP 2006-44261 A [Patent Document 4] JP 2019-38939 A Summary of the Invention [Problem to be solved by the invention]

[0011] However, although Patent Document 1 describes a method of obtaining a fiber-reinforced composite material by disposing a molten thermoplastic resin substrate on a thermosetting prepreg, the molten thermoplastic resin substrate is difficult to handle, and in order to combine the thermoplastic resin substrate and the thermosetting prepreg, it is necessary to control the molding conditions. Furthermore, since only the thermoplastic resin exists on the surface layer, it is difficult to control warpage.

[0012] The fiber-reinforced resin sheet described in Patent Document 2 is a substrate having weldability in which a thermoplastic resin layer and an adhesive layer are firmly bonded together. However, since the reinforcing fibers constituting the sheet are discontinuous and in the form of a nonwoven fabric, the mechanical properties of the substrate do not necessarily satisfy the requirements of the industrial field.

[0013] Patent Document 3 discloses a fiber-reinforced composite material in which a thermosetting resin is injected simultaneously or subsequently into a reinforcing fiber sheet partially impregnated with a thermoplastic resin. However, this is a fiber-reinforced composite material for RTM molding, and does not function as an uncured prepreg and has no flexibility, so it does not satisfy the requirements for a substrate.

[0014] Patent Document 4 discloses a prepreg having a thermoplastic resin on the surface layer, but the thermoplastic resin is not added for the purpose of thermal welding, and does not meet the requirements for joining applications.

[0015] For the above reasons, there has been an urgent need to provide a composite prepreg that has excellent mechanical properties and handleability, in which a fiber-reinforced thermoplastic resin layer and a thermosetting resin layer are firmly adhered to each other while exhibiting secondary weldability (thermal weldability) with other components. [Means for solving the problem]

[0016] In order to solve the above problems, the present invention mainly has any one of the following configurations. (1) A composite prepreg in which a thermoplastic resin and a thermosetting resin are impregnated into reinforcing fibers, and a thermoplastic resin layer and a thermosetting resin layer are formed and bonded to each other by forming an interface, A thermoplastic resin layer is present on at least one surface, and the thermoplastic resin layer contains continuous reinforcing fibers; In a cross section perpendicular to the plane direction, reinforcing fibers are distributed in an area of ​​80% or more of the thickness of each of the thermoplastic resin layer and the thermosetting resin layer, and a composite prepreg in which the adhesive strength between the thermoplastic resin layer and the thermosetting resin layer is 1N / 24mm or more. (2) A method for producing a composite prepreg, comprising stacking a thermoplastic semipreg, in which continuous reinforcing fibers are impregnated with a thermoplastic resin while leaving unimpregnated areas on the surface, and a thermosetting prepreg, in which reinforcing fibers are impregnated with a thermosetting resin, so that the thermoplastic semipreg is in contact with the unimpregnated areas, and then heating and pressing the laminate. (3) A method for manufacturing a composite prepreg, comprising laminating a thermoplastic prepreg, in which continuous reinforcing fibers are impregnated with a thermoplastic resin having a melting temperature of 180°C or lower, and a thermosetting prepreg, in which reinforcing fibers are impregnated with a thermosetting resin, and then heating and pressing the laminate. (4) A fiber-reinforced resin molded body in which a thermoplastic resin and a thermosetting resin are impregnated into reinforcing fibers to form a thermoplastic resin layer and a thermosetting resin layer that are bonded to each other by forming an interface, A thermoplastic resin layer is present on at least one surface, and the thermoplastic resin layer contains continuous reinforcing fibers; In a cross section perpendicular to the plane direction, reinforcing fibers are distributed in an area of ​​80% or more of the thickness of each of the thermoplastic resin layer and the thermosetting resin layer, and a fiber-reinforced resin molding in which the adhesive strength between the thermoplastic resin layer and the thermosetting resin layer is 1 N / 24 mm or more. Effect of the Invention

[0017] In the composite prepreg of the present invention, since reinforcing fibers are dispersed not only in the thermosetting resin layer but also in the thermoplastic resin layer, it exhibits excellent mechanical properties, has small warpage as a prepreg, and is excellent in handleability. In addition, even when a molded body is formed using this prepreg, since the thermoplastic resin layer and the thermosetting resin layer are firmly bonded to each other, the thermoplastic resin layer and the thermosetting resin layer are not easily peeled off during molding. In addition, since the thermoplastic resin layer in the prepreg of the present invention contains continuous reinforcing fibers, it is also excellent in secondary welding with other members. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a schematic diagram showing how to take a cross section when calculating the roughness average length RSm and roughness average height Rc of a curve formed by the interface of a resin layer in a composite prepreg according to the present invention. [Diagram 2] FIG. 2 is a schematic diagram of an observation cross section of a composite prepreg according to the present invention. [Diagram 3] FIG. 2 is a schematic diagram of an observation cross section of a composite prepreg according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention will now be described.

[0020] <Composite prepreg> The composite prepreg of the present invention (hereinafter sometimes simply referred to as "prepreg") is formed by impregnating reinforcing fibers with a thermoplastic resin and a thermosetting resin to form a thermoplastic resin layer and a thermosetting resin layer that are bonded to each other by forming an interface, and the thermoplastic resin layer is present on the surface of the prepreg.

[0021] FIG. 2 shows one embodiment of the composite prepreg of the present invention, and is a schematic diagram showing a cross section cut at an angle of 45 degrees to the orientation direction of the continuous reinforcing fibers 2 as shown in FIG. 1 and perpendicular to the surface direction of the composite prepreg (or molded body). In FIG. 2, a large number of reinforcing fibers 7 are present, oriented at an angle of 45 degrees from the direction perpendicular to the paper. The group of reinforcing fibers 7 is impregnated with a thermoplastic resin and a thermosetting resin to form a thermosetting resin layer 9 and a thermoplastic resin layer 8. The thermosetting resin layer 9 and the thermoplastic resin layer 8 are in contact with each other while forming an interface 10. As shown in FIG. 2, in the present invention, the thermoplastic resin layer 8 is present on at least one surface of the composite prepreg.

[0022] The thermoplastic resin layer contains continuous reinforcing fibers. The continuous reinforcing fibers need only be continuous in at least one direction (for example, the longitudinal direction of the composite prepreg), and are preferably continuous over the entire length, since this not only provides higher mechanical properties but also makes the prepreg less likely to break during use and improves handling properties. In particular, when the prepreg is welded to another member via the thermoplastic resin layer, the reinforcing fibers contained in the thermoplastic resin layer are continuous reinforcing fibers, which reinforces the bonding interface and improves bonding strength. The reinforcing fibers contained in the thermoplastic resin layer may be partially broken along the way, but it is preferable that 90% by mass or more of the reinforcing fibers are continuous reinforcing fibers. .Ma In addition, the thermoplastic resin layer preferably has reinforcing fibers that are continuous in the width direction of the composite prepreg.

[0023] One example of a method for determining whether the reinforcing fibers contained in the thermoplastic resin layer are continuous or not is to cut the obtained composite prepreg into a 200 mm square, dissolve the thermosetting resin in a solvent, remove the exposed fibers, and then heat it at 450°C for 30 minutes in a nitrogen atmosphere to burn off the thermoplastic resin and check the remaining reinforcing fibers.

[0024] In the thermoplastic resin layer, the reinforcing fibers are preferably arranged in one or more layers in a unidirectionally oriented state, or arranged in a woven structure. In order to obtain a lightweight and more durable molded product, it is more preferable that the reinforcing fibers are arranged in multiple layers oriented in one direction.

[0025] On the other hand, the reinforcing fibers contained in the thermosetting resin layer may be continuous or discontinuous. Continuous reinforcing fibers are preferable because the mechanical properties of the resulting composite prepreg are improved. Discrete reinforcing fibers are preferable because the flexibility and formability of the resulting composite prepreg are improved. From the viewpoint of the mechanical properties of the resulting composite prepreg, particularly the tensile strength, it is more preferable that the thermosetting resin layer contains continuous reinforcing fibers, and it is even more preferable that 90% or more of the reinforcing fibers contained in the thermosetting resin layer are continuous reinforcing fibers. As an example of a method for determining whether the reinforcing fibers contained in the thermosetting resin layer are continuous reinforcing fibers, the obtained composite prepreg is cut into 200 mm squares, the thermosetting resin is dissolved with a solvent, and the exposed fibers are collected and judged.

[0026] In the thermosetting resin layer, the reinforcing fibers are preferably present in any one of the following forms: reinforcing fibers cut to a fixed or variable length are randomly oriented, reinforcing fibers cut to a fixed or variable length are arranged with a specific anisotropy, reinforcing fibers oriented in one direction are arranged in one or more layers, or reinforcing fibers arranged in a woven structure. In order to obtain a lightweight and more durable molded body, the reinforcing fibers are preferably present in a form in which reinforcing fibers oriented in one direction are arranged in multiple layers.

[0027] The reinforcing fibers contained in the thermoplastic resin layer have a surface free energy of 10 to 50 mJ / m2 as measured by the Wilhelmy method. 2By using reinforcing fibers controlled within this range, not only can the reinforcing fibers be firmly bonded to the thermoplastic resin to improve the mechanical properties, but also when a part of the reinforcing fibers contained in the thermoplastic resin layer contacts the thermosetting resin layer, it exhibits high affinity with the thermosetting resin. The surface free energy of the reinforcing fibers is more preferably 10 to 40 mJ / m 2 , more preferably 20 to 40 mJ / m 2 10mJ / m 2 If it is less than 50 mJ / m, the affinity between the reinforcing fiber and the thermosetting resin or thermoplastic resin will be low, and the strength of the thermoplastic resin layer or the adhesive strength between the thermoplastic resin layer and the thermosetting resin layer will be insufficient. 2 If the density exceeds 100%, the reinforcing fibers will aggregate together, resulting in poor dispersion in the molded product and large variations in bonding strength.

[0028] In addition, the reinforcing fibers contained in the thermosetting resin layer are also preferably those having a surface free energy of 10 to 50 mJ / m as measured by the Wilhelmy method. 2 By using reinforcing fibers controlled within this range, not only can the reinforcing fibers be firmly bonded to the thermosetting resin to improve the mechanical properties, but also when a part of the reinforcing fibers contained in the thermosetting resin layer comes into contact with the thermoplastic resin layer, it exhibits high affinity with the thermoplastic resin.

[0029] Methods for controlling the surface free energy of reinforcing fibers include a method of controlling the surface free energy by oxidizing the fiber surface and adjusting the amount of oxygen-containing functional groups such as carboxyl groups and hydroxyl groups, and a method of controlling the surface free energy by attaching a single compound or multiple compounds to the fiber surface. When multiple compounds are attached to the fiber surface, compounds with high and low surface free energies may be mixed and attached.

[0030] Examples of such compounds include polyhydric alcohol fatty acid esters, polyoxyalkylenes, bisphenol A-alkylene oxide adducts, sorbitol-type polyglycidyl ethers, glycerol-type polyglycidyl ethers, polyethylene glycol diglycidyl ethers, glycidyl benzamide, amide-modified epoxy, urea-modified epoxy, glycidyl phthalimide, urethane-modified epoxy, and amine compounds such as polyethyleneimine and polyallylamine, which may be used alone or in combination.

[0031] Hereinafter, a method for calculating the surface free energy of reinforcing fibers will be described.

[0032] The surface free energy can be calculated by measuring the contact angle of the reinforcing fiber with each of three types of solvents (purified water, ethylene glycol, and tricresyl phosphate), and then using Owens' approximation formula to calculate the surface free energy. The procedure is shown below, but the measurement equipment and detailed method are not necessarily limited to those shown below.

[0033] Using a DataPhysics DCAT11, first, one single fiber is taken from the reinforcing fiber bundle and cut into eight pieces with a length of 12±2 mm, then attached in parallel to a dedicated holder FH12 (a flat plate with a surface coated with an adhesive substance) with 2-3 mm between each single fiber. The tips of the single fibers are then cut and set in the DCAT11 holder. For the measurement, a cell containing each solvent is brought close to the bottom ends of the eight single fibers at a speed of 0.2 mm / s, and the single fibers are immersed up to 5 mm from their tips. The single fibers are then pulled up at a speed of 0.2 mm / s. This operation is repeated four or more times. The force F that the single fiber receives while immersed in the liquid is measured with an electronic balance. This value is used to calculate the contact angle θ using the following formula. COSθ = (force F (mN) acting on 8 single fibers) / (8 (number of single fibers) × circumference of single fiber (m) × surface tension of solvent (mJ / m 2 )) The measurement is performed on single fibers extracted from three different positions of the reinforcing fiber bundle, i.e., the average contact angle is calculated for a total of 24 single fibers for one reinforcing fiber bundle.

[0034] Surface free energy of reinforcing fiber γ f is the polar component of the surface free energy γ p f , and the non-polar component of the surface free energy γ d f It is calculated as the sum of

[0035] Polar component of surface free energy γ p f The non-polar component of the surface free energy γ is calculated by approximating the surface tension and contact angle of each liquid by the Owens approximation formula shown below (a formula consisting of the polar and non-polar components of the surface tension specific to each solvent, and the contact angle θ), plotting it on X and Y, and then approximating it linearly using the least squares method. d f is calculated by squaring the intercept b. The surface free energy of the reinforcing fiber γ f is the sum of the square of the slope a and the square of the intercept b. Y = a X + b X = √(polar component of the surface tension of the solvent (mJ / m 2 )) / √(non-polar component of the solvent's surface tension (mJ / m 2 )) Y = (1 + COSθ) (polar component of the surface tension of the solvent (mJ / m 2 )) / 2√(non-polar component of the solvent's surface tension (mJ / m 2 )) The polar component of the surface free energy of the reinforcing fiber, γ p f =a 2 The non-polar component of the surface free energy of the reinforcing fiber, γ d f =b 2 Total surface free energy γ f =a 2 +b 2

[0036] The polar and non-polar components of the surface tension for each solvent are as follows: ·Purified water Surface tension 72.8mJ / m 2 , polar component 51.0mJ / m 2 , non-polar component 21.8 (mJ / m 2 ) Ethylene glycol Surface tension 48.0mJ / m 2 , polar component 19.0mJ / m 2 , non-polar component 29.0 (mJ / m 2 ) Tricresol phosphate Surface tension 40.9mJ / m 2 , polar component 1.7mJ / m 2 , non-polar component 39.2 (mJ / m 2 )

[0037] In the composite prepreg of the present invention, the presence of a thermoplastic resin layer on at least one surface makes the composite prepreg easy to weld to other members (has secondary weldability). Furthermore, it is preferable that a thermosetting resin layer is present on the other surface. The presence of a thermosetting resin layer on the other surface is preferable because the composite prepreg of the present invention exhibits tackiness derived from the thermosetting resin.

[0038] Examples of the reinforcing fibers contained in the thermoplastic resin layer or the thermosetting resin layer include glass fibers, carbon fibers, metal fibers, aromatic polyamide fibers, polyaramid fibers, alumina fibers, silicon carbide fibers, boron fibers, and basalt fibers. These may be used alone or in combination of two or more types. These reinforcing fibers may be surface-treated. Examples of surface treatments include metal cladding treatment, treatment with a coupling agent, treatment with a sizing agent, and additive attachment treatment. These reinforcing fibers also include conductive reinforcing fibers. As the reinforcing fibers, carbon fibers are preferably used from the viewpoint that they have a small specific gravity, high strength, high elastic modulus, and a small linear expansion coefficient, which can reduce the difference in the fiber expansion coefficient between the thermoplastic resin and the thermosetting resin and reduce the warping of the prepreg. Commercially available carbon fibers include "TORAYCA (registered trademark)" T800G-24K, "TORAYCA (registered trademark)" T800S-24K, "TORAYCA (registered trademark)" T700G-24K, "TORAYCA (registered trademark)" T700S-24K, "TORAYCA (registered trademark)" T300-3K, and "TORAYCA (registered trademark)" T1100G-24K (all manufactured by Toray Industries, Inc.).

[0039] The reinforcing fibers mainly contained in the thermoplastic resin layer and the thermosetting resin layer may have different properties. Such a prepreg can be produced by using different reinforcing fibers for the thermoplastic prepreg and the thermosetting prepreg before bonding in the manufacturing method described below. Such a prepreg can impart different properties to the thermoplastic resin layer and the thermosetting resin layer. However, it is more preferable to use common (having the same properties) reinforcing fibers for the thermoplastic resin layer and the thermosetting resin layer in order to reduce the difference in linear expansion coefficient between the thermoplastic resin layer and the thermosetting resin layer and to reduce warpage.

[0040] The reinforcing fibers contained in the thermoplastic resin layer or the thermosetting resin layer preferably have a strand tensile strength of 5.5 GPa or more measured according to the resin-impregnated strand test method of JIS R7608 (2007), because a molded product having excellent bonding strength in addition to tensile strength can be obtained. It is even more preferable that the strand tensile strength is 5.8 GPa. The bonding strength referred to here refers to the tensile shear bonding strength obtained according to ISO4587:1995 (JIS K6850 (1994)).

[0041] In the composite prepreg of the present invention, the amount of reinforcing fibers per unit area in the surface direction is 30 to 2,000 g / m 2 It is preferable that the amount of reinforcing fibers is 30 g / m 2 When the amount of reinforcing fibers is 2,000 g / m or more, the number of layers required to obtain a desired thickness during the production of a molded body can be reduced, and the work can be simplified. 2 When it is equal to or less than this, the drape property of the prepreg is likely to be improved.

[0042] The mass content of the reinforcing fiber of the composite prepreg of the present invention is preferably 30 to 90% by mass, more preferably 35 to 85% by mass, and even more preferably 40 to 80% by mass. When the mass content of the reinforcing fiber is 30% by mass or more, the amount of resin is not too large compared to the fiber, and the advantage of a molded body having excellent specific strength and specific elastic modulus is easily obtained, and when molding a molded body, the amount of heat generated during curing is not likely to be excessively high. In addition, when the mass content of the reinforcing fiber is 90% by mass or less, impregnation of the resin during prepreg production is unlikely to occur, and the voids in the obtained molded body are likely to be reduced. As a method for measuring the mass content of the reinforcing fiber, the obtained composite prepreg is cut into a 200 mm square and the mass is measured. Thereafter, the thermosetting resin and the thermoplastic resin are burned off by heating at 450°C for 30 minutes in a nitrogen atmosphere, and the mass of the remaining reinforcing fiber is measured, and the ratio [%] of the mass after burning off to the mass before burning off is obtained.

[0043] In the composite prepreg of the present invention, the volume content of the reinforcing fibers in the thermoplastic resin layer is preferably 10% or more. Furthermore, it is preferably 10 to 99%, more preferably 20 to 95%, and particularly preferably 40% to 70%. By setting it in such a range, not only can the mechanical properties of the prepreg be improved, but also the flow of the thermoplastic resin can be suppressed when bonding with the thermosetting resin layer in the production of the composite prepreg. Furthermore, when bonding the composite prepreg of the present invention to other members, bonding can be performed while suppressing the flow of the thermoplastic resin by having the reinforcing fibers present in the above range. The method for measuring the volume content of the reinforcing fibers in the thermoplastic resin layer includes a method in which a segmentation analysis is performed using an X-ray CT image of a small piece of the composite prepreg of the present invention in which the thermosetting resin is cured, and the volume of the reinforcing fibers present in the thermoplastic resin layer region is divided by the total volume of the thermoplastic resin layer to obtain the ratio [%]. The composite prepreg used for the measurement may be dyed in order to adjust the contrast between the thermoplastic resin layer and the thermosetting resin layer during observation.

[0044] In the composite prepreg of the present invention, when a cross section perpendicular to the plane direction of the prepreg is observed, the reinforcing fibers are preferably distributed in an area of ​​80% or more of the thickness of each of the thermoplastic resin layer and the thermosetting resin layer. By setting the range in this way, the fibers are distributed almost evenly in the prepreg, so that not only can the tensile strength of the prepreg be improved, but also the warp of the prepreg can be reduced by distributing the fibers almost evenly throughout the prepreg. From the viewpoint of further improving the tensile strength of the prepreg, it is more preferable that the reinforcing fibers are distributed in an area of ​​90% or more of the thickness of each of the thermoplastic resin layer and the thermosetting resin layer.

[0045] Here, the distribution area of ​​the reinforcing fibers in each layer can be determined by the following method, for example. First. After the thermosetting resin is cured, the presence or absence of reinforcing fibers is determined in the area divided every 20 μm in the thickness direction of the entire prepreg in the cross-sectional image obtained using X-ray CT. The thickness of the thermoplastic resin layer or the thermosetting resin layer is the maximum value of the thickness at which the thermoplastic resin contained in the thermoplastic resin layer of interest or the thermosetting resin contained in the thermosetting resin layer exists in the cross-sectional image. Here, the thickness of the thermoplastic resin layer and the thermosetting resin layer will be explained using FIG. 3, which is a schematic diagram of the observed cross section of the composite prepreg according to the present invention. In the cross-sectional image 14 perpendicular to the surface direction of the prepreg, the reinforcing fiber 7, the thermoplastic resin layer 8, the thermosetting resin layer 9, and another thermoplastic resin layer 17 are shown. In this cross-sectional image 14, the thickness 16 of the thermoplastic resin layer is the maximum value of the thickness of the part where the thermoplastic resin contained in the thermoplastic resin layer 8 penetrates most deeply into the adjacent thermosetting resin layer 9 from the prepreg surface 15. Similarly, in this cross-sectional image 14, the thermosetting resin layer 9 is adjacent to the thermoplastic resin layer 8 and another thermoplastic resin layer 17, and the maximum value of the thickness of the portion where the thermosetting resin contained in the thermosetting resin layer 9 penetrates most deeply into the thermoplastic resin layer 8 and the other thermoplastic resin layer 17 is taken as the thickness 18 of the thermosetting resin layer. For each of the thermoplastic resin layer and the thermosetting resin layer, the fiber dispersion within the thickness range is determined.

[0046] In the composite prepreg of the present invention, the coefficient of variation Q of the volume content of the reinforcing fiber per unit section of 0.05 mm square in the thermoplastic resin layer is preferably 40% or less. If the coefficient of variation Q is 40% or less, the fibers are evenly distributed in the thermoplastic resin layer, and the resin-rich portion is suppressed. In the joining process with other thermoplastic resin members welded through the thermoplastic resin layer, or in the composite process of the thermoplastic prepreg and the thermosetting prepreg during the production of this prepreg, not only can the flow of the thermoplastic resin be suppressed, but also the warp of the prepreg obtained is reduced and the mechanical properties of the prepreg are improved due to the uniform arrangement of the fibers. Furthermore, in the joining with other thermoplastic resin members welded through the thermoplastic resin layer, the variation in the joining strength and the fracture mode is suppressed. The coefficient of variation Q is more preferably 30% or less, and even more preferably 10% or less. There is no particular limit to the lower limit of the coefficient of variation Q, but the closer to zero, the more evenly the fibers are dispersed, which is preferable from the viewpoint of the production of the prepreg and the joining with other members.

[0047] The coefficient of variation Q can be measured by performing segmentation analysis using an X-ray CT image of a small piece of the composite prepreg of the present invention in which the thermosetting resin has been cured, measuring the volume of the reinforcing fibers present per 0.05 mm unit section in the thermoplastic resin layer, dividing the volume of the reinforcing fibers by the volume of the 0.05 mm unit section at 100 locations, calculating the standard deviation and average value, and dividing the standard deviation by the average value. Alternatively, the prepreg is cut along the thickness direction, and the fiber content of the reinforcing fibers per 0.05 mm unit section in the thermoplastic resin layer at 10 locations on the cut surface is measured, calculating the standard deviation and average value, and dividing the standard deviation by the average value.

[0048] The coefficient of variation R of the volume content of the reinforcing fiber per unit section of 0.05 mm square in the thermosetting resin layer can also be calculated in the same manner as the coefficient of variation Q of the reinforcing fiber in the thermoplastic resin layer described above. The coefficient of variation R is also preferably 40% or less, more preferably 30% or less, and even more preferably 10% or less, similar to the coefficient of variation Q, from the viewpoints of suppressing the resin flow of the thermosetting resin when the thermoplastic prepreg and the thermosetting prepreg are combined, suppressing the flow of the thermosetting resin when joined to other resin members, joint strength, and stabilization of the fracture shape.

[0049] In the composite prepreg of the present invention, the adhesive strength between the thermoplastic resin layer and the thermosetting resin layer is 1 N / 24 mm or more. This range is preferable because the thermosetting resin layer is less likely to peel off from the thermoplastic resin layer when handling the prepreg. From the same viewpoint, the adhesive strength between the thermoplastic resin layer and the thermosetting resin layer is more preferably 10 N / 24 mm or more, and although there is no particular upper limit, 100 N / 24 mm is sufficient for practical use.

[0050] The adhesive strength can be determined as follows: According to JIS Z0237 (2009), the prepreg is cut to a width of 24 mm and a length of 300 mm, and a thermosetting resin layer is bonded to a flat plate made of SUS material to prepare a test piece. The thermoplastic resin layer of this test piece is peeled in a 180 degree direction at a speed of 300 mm / min, and the simple average value of the load at that time is taken as the adhesive strength.

[0051] In the composite prepreg of the present invention, it is preferable that the interface between the thermosetting resin layer and the thermoplastic resin layer has the following shape. That is, as shown in Fig. 1, when the prepreg is observed at a cross section perpendicular to the plane direction of the prepreg, which is at an angle of 45 degrees to the orientation direction of the continuous reinforcing fibers (when the reinforcing fibers are in a woven form, an angle of 45 degrees to any fiber constituting the woven fabric), the roughness average length RSm of the curve formed by the interface between both resin layers (hereinafter referred to as "interface curve") is 100 μm or less, and the roughness average height Rc is 3.5 μm or more. Here, the roughness average length RSm and the roughness average height Rc are parameters that represent the roughness of the profile curve measured according to JIS B0601 (2013).

[0052] In such cross-sectional observation, when the roughness average length RSm of the interface curve is 100 μm or less, not only the chemical and / or physical bonding force but also the mechanical bonding force of entanglement is added, and the thermoplastic resin layer and the thermosetting resin layer are difficult to peel off. The lower limit is not particularly limited, but is preferably 15 μm or more from the viewpoint of avoiding a decrease in the mechanical bonding force due to stress concentration.

[0053] In addition, by having the interface curve roughness average height Rc of 3.5 μm or more, not only is mechanical bonding strength due to entanglement expressed, but the reinforcing fibers present at the interface are chemically or / and physically bonded to the thermoplastic resin and the thermosetting resin, and the adhesive strength between the thermoplastic resin layer and the thermosetting resin layer is improved, which is preferable. A more preferable range of the interface curve roughness average height Rc is 10 μm or more, in which the reinforcing fibers contained in one resin layer are easily contained in the other resin layer, and the adhesive strength is further improved, and particularly preferably 20 μm or more. The upper limit is not particularly limited, but is preferably 100 μm or less from the viewpoint of avoiding a decrease in mechanical bonding strength due to stress concentration.

[0054] One example of a manufacturing method that achieves the Rc and RSm is a manufacturing method in which a thermoplastic semipreg is prepared in which continuous reinforcing fibers are impregnated with a thermoplastic resin while leaving unimpregnated areas on the surface, and a thermosetting prepreg in which reinforcing fibers are impregnated with a thermosetting resin is laminated on the thermoplastic semipreg so that it is in contact with the unimpregnated areas of the thermoplastic semipreg, and then heated and pressurized, as described below.

[0055] Here, the roughness average height Rc and roughness average length RSm of the interface curve can be measured by a known method. For example, a method of measuring from a cross-sectional image obtained by X-ray CT after curing the thermosetting resin, a method of measuring from an elemental analysis mapping image by an energy dispersive X-ray spectrometer (EDS), or a method of measuring from a cross-sectional image by an optical microscope, a scanning electron microscope (SEM), or a transmission electron microscope (TEM) can be mentioned. In the observation, the thermoplastic resin and / or the thermosetting resin may be dyed to adjust the contrast. In the image obtained by any of the above methods, the roughness average height Rc and roughness average length RSm of the interface curve are measured in a range of 500 μm square.

[0056] The method for measuring the roughness average height Rc and roughness average length RSm of the interface curve (method 1 for measuring interface curve elements) is shown in FIG. 2. Using the end 11 on the thermosetting resin layer side of the rectangular cross-sectional image 6 as a reference line, vertical base lines 12 are drawn at 5 μm intervals from the thermosetting resin layer 9 toward the thermoplastic resin layer 8. The point where the vertical base line drawn from the reference line first intersects with the thermoplastic resin is plotted, and the line connecting the plotted points is defined as the interface curve 13. The obtained interface curve 13 is subjected to a filtering process based on JIS B0601 (2013), and the roughness average height Rc and roughness average length RSm of the interface curve 13 are calculated.

[0057] In the present invention, examples of the thermoplastic resin include polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate, and liquid crystal polyester, polyolefins such as polyethylene, polypropylene, and polybutylene, styrene-based resins, and urethane resins, as well as polyoxymethylene, polyamide 6, polyamide 66, and other polyamides, polycarbonate, polymethyl methacrylate, polyvinyl chloride, polyarylene sulfides such as polyphenylene sulfide, polyphenylene ether, modified polyphenylene ether, polyimide, polyamideimide, polyetherimide, polysulfone, modified polysulfone, polyethersulfone, polyarylene ether ketones such as polyketone, polyether ketone, polyether ether ketone, and polyether ketone ketone, polyarylate, polyether nitrile, phenolic resins, and phenoxy resins. These thermoplastic resins may also be copolymers or modified bodies of the above-mentioned resins, and / or resins obtained by blending two or more of them. In this specification, the term "thermoplastic resin" is used to include compositions containing fillers and additives.

[0058] Among these, in terms of the balance between moldability, heat resistance, and mechanical properties, it is preferable to use at least one thermoplastic resin selected from the group consisting of polyolefins, polycarbonates, polyesters, polyarylene sulfides, polyamides, polyoxymethylene, polyetherimides, polyethersulfones, and polyarylene ether ketones.

[0059] Furthermore, other fillers and additives may be appropriately contained depending on the application, etc., within the scope of not impairing the object of the present invention. Examples include inorganic fillers, flame retardants, conductivity imparting agents, crystal nucleating agents, ultraviolet absorbers, antioxidants, vibration dampers, antibacterial agents, insect repellents, deodorants, coloring inhibitors, heat stabilizers, release agents, antistatic agents, plasticizers, lubricants, colorants, pigments, dyes, foaming agents, foam control agents, coupling agents, etc.

[0060] In the present invention, examples of the thermosetting resin include unsaturated polyester resin, vinyl ester resin, epoxy resin, phenol resin, urea resin, melamine resin, polyimide resin, cyanate ester resin, bismaleimide resin, benzoxazine resin, copolymers thereof, modified products thereof, and resins obtained by blending at least two of these. In order to improve impact resistance, an elastomer or rubber component may be added to the thermosetting resin. Among these, epoxy resin is preferable because of its excellent mechanical properties, heat resistance, and adhesion to reinforcing fibers. Examples of the base resin of the epoxy resin include bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD ​​type epoxy resin, and bisphenol S type epoxy resin; brominated epoxy resins such as tetrabromobisphenol A diglycidyl ether; epoxy resins having a biphenyl skeleton, epoxy resins having a naphthalene skeleton, epoxy resins having a dicyclopentadiene skeleton, novolac type epoxy resins such as phenol novolac type epoxy resin and cresol novolac type epoxy resin; Examples of the epoxy resins include glycidyl amine type epoxy resins such as phenol, N,N,O-triglycidyl-p-aminophenol, N,N,O-triglycidyl-4-amino-3-methylphenol, N,N,N',N'-tetraglycidyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, N,N-diglycidylaniline, and N,N-diglycidyl-o-toluidine, resorcinol diglycidyl ether, and triglycidyl isocyanurate.

[0061] Examples of the curing agent for the epoxy resin include dicyandiamide, aromatic amine compounds, phenol novolac resins, cresol novolac resins, polyphenol compounds, imidazole derivatives, tetramethylguanidine, thiourea-added amines, carboxylic acid hydrazides, carboxylic acid amides, and polymercaptans.

[0062] In this specification, the term "thermosetting resin" also includes compositions containing a curing agent and additives.

[0063] <Method of manufacturing composite prepreg> The composite prepreg of the present invention can be produced, for example, by a production method in which a thermoplastic semipreg in which continuous reinforcing fibers are impregnated with a thermoplastic resin while leaving an unimpregnated region on the surface is prepared, a thermosetting prepreg in which reinforcing fibers are impregnated with a thermosetting resin is laminated on the thermoplastic semipreg so as to be in contact with the unimpregnated region of the thermoplastic semipreg, and then heated and pressed. By using such a semipreg, the unimpregnated region of the semipreg is impregnated with the thermosetting resin contained in the thermosetting prepreg during compounding, and the thermoplastic resin layer and the thermosetting resin layer can be firmly bonded.

[0064] The impregnation rate of the thermoplastic resin in the thermoplastic semipreg is preferably 97% or less, more preferably 90% or less. The lower the impregnation rate, the more voids contained in the semipreg, and in the subsequent compounding process, the thermosetting resin impregnates the voids and develops strong adhesive strength. The lower limit of the impregnation rate is not particularly limited, but from the viewpoint of reducing the voids remaining in the composite prepreg after compounding, it is preferably 50% or more, and from the viewpoint of making the compounding process easier, it is preferably 60% or more. Here, the impregnation rate is a value calculated by the following formula (1) when the total cross-sectional area of ​​the fiber reinforced resin substrate including the voids in the thermoplastic prepreg is A0 and the cross-sectional area of ​​the voids is A1 in the cross-sectional observation in the thickness direction of the thermoplastic semipreg. Impregnation rate = (A0-A1) / A0 × 100 (1)

[0065] Another method for producing the composite prepreg of the present invention includes preparing a thermoplastic prepreg in which continuous reinforcing fibers are impregnated with a thermoplastic resin having a melting temperature of 180° C. or less, laminating a thermosetting prepreg in which reinforcing fibers are impregnated with a thermosetting resin on the thermoplastic prepreg, and heating and pressurizing the prepreg at a temperature within the curing reaction temperature range of the thermosetting resin and above the melting temperature of the thermoplastic resin. The melting temperature of a thermoplastic resin refers to the melting point in the case of a crystalline thermoplastic resin and the glass transition temperature in the case of an amorphous thermoplastic resin, and can be measured as follows. The peak value of the melting temperature of a thermoplastic resin is measured in accordance with the "Method of Measuring Transition Temperature of Plastics" specified in JIS K7121 (1987). Before the measurement, the sample is dried for 24 hours or more in a vacuum dryer controlled at a furnace temperature of 50° C. as a sample adjustment, and the melting temperature according to the above standard is obtained using a differential scanning calorimeter, and the peak top is defined as the melting temperature. By using such a thermoplastic resin, when the thermoplastic prepreg and the thermosetting prepreg are heated and pressurized at a temperature equal to or higher than the melting temperature of the thermoplastic resin in the process of combining the thermoplastic prepreg and the thermosetting prepreg, the thermoplastic prepreg is less likely to lose its shape because it contains reinforcing fibers, but the thermoplastic resin and the thermosetting resin flow and mix near the boundary with the thermosetting prepreg, thereby exhibiting strong adhesive strength.

[0066] <Fiber-reinforced resin molding> Another aspect of the present invention is a fiber-reinforced resin molded body in which a thermoplastic resin and a thermosetting resin are impregnated into a reinforcing fiber, and a thermoplastic resin layer and a thermosetting resin layer are formed by forming an interface and bonding each other, and a thermoplastic resin layer is present on at least one surface, the thermoplastic resin layer contains continuous reinforcing fibers, and in a cross section perpendicular to the surface direction, the reinforcing fibers are distributed in an area of ​​80% or more of the thickness of each layer of the thermoplastic resin layer and the thermosetting resin layer, and the adhesive strength between the thermoplastic resin layer and the thermosetting resin layer is 1N / 24mm or more. The internal form of such a fiber-reinforced resin molded body is the same as that of the composite prepreg described above except that the thermosetting resin is cured, so a description will be omitted. In addition, the method of determining the adhesive strength is the same as that of the composite prepreg described above.

[0067] Such a fiber-reinforced resin molded article can be produced by heating and pressurizing the above-mentioned composite prepreg. Examples of the method for heating and pressurizing include press molding, autoclave molding, bagging molding, wrapping tape method, and internal pressure molding.

[0068] More specific methods for molding the fiber-reinforced resin molding of the present invention include methods in which the above-mentioned composite prepreg of the present invention is laminated alone or together with other prepregs and molded by press molding, autoclave molding, bagging molding, wrapping tape method, internal pressure molding, etc., and methods in which the composite prepreg of the present invention and other fiber-reinforced resin substrates or fiber substrates are used to mold by hand lay-up, filament winding, pultrusion, resin injection molding, resin transfer molding, etc. EXAMPLES

[0069] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to these examples. The unit "parts" in the composition ratio means parts by mass unless otherwise noted. Furthermore, the measurements of various properties were performed under an environment of a temperature of 23°C and a relative humidity of 50% unless otherwise noted.

[0070] (1) Adhesive strength The composite prepregs produced in each Example and Comparative Example were cut to a width of 24 mm and a length of 300 mm to prepare test pieces. These test pieces were fixed to a flat plate made of stainless steel, and the thermoplastic resin layer was peeled in a 180° direction at a speed of 300 mm / min in accordance with JIS Z0237 (2009). The simple average value of the load at this time was taken as the adhesive strength.

[0071] (2) Fiber dispersion The composite prepreg prepared in each Example and Comparative Example was sandwiched between the surfaces of two smooth polytetrafluoroethylene resin plates, and the thermosetting resin contained in the prepreg was gradually cured at 40°C for 10 days. After curing, a small piece of 20 mm square was cut out from the prepreg, embedded in epoxy resin, and polished so that the cross section perpendicular to the orientation direction of the reinforcing fibers became the observation surface to prepare a sample. The sample was magnified 400 times with a laser microscope (Keyence Corporation, VK-9510) to observe the fiber dispersion in the thickness direction. The dispersion was judged by judging the presence or absence of fibers in 20 mm wide areas divided every 20 μm in the thickness direction of the prepreg in the sample cross section, and for both the thermoplastic resin layer and the thermosetting resin layer, if the area where fibers existed exceeded 80% in both layers, it was judged as "good", and if it did not exceed that in either layer or both layers, it was judged as "poor".

[0072] (3) Coefficient of variation Q The composite prepreg prepared in each Example and Comparative Example was sandwiched between the surfaces of two smooth polytetrafluoroethylene resin plates, and the thermosetting resin contained in the prepreg was gradually cured at 40°C for 10 days. After curing, a sample with a width of 15 mm and a length of 100 mm was cut from the prepreg, and photographed with an X-ray CT device at a FOV of 500 μm, and a segmentation analysis was performed. The measurement device used was an X-ray microscope "nano3DX (registered trademark)" (manufactured by Rigaku Corporation). From the analysis results, the ratio [%] of the volume of the reinforcing fiber present per 0.05 mm unit section in the thermoplastic resin layer divided by the volume of the 0.05 mm unit section was measured for 100 points, and the standard deviation and average value were calculated, and the value obtained by dividing the standard deviation by the average value was used as the coefficient of variation Q.

[0073] (4) Tensile strength of molded body The measurements were made based on the ISO527-3 method (1995). The composite prepreg made in each Example and Comparative Example was cut into two pieces of 300 mm square. The two cut prepregs were laminated so that the fiber orientation direction was the same and the thermosetting resin layers were in contact with each other, and autoclave molding was performed under conditions of 130°C, 2 hours, and 0.6 MPa to obtain a molded body in which the thermosetting resin was cured. Test pieces were made by cutting out any of the molded bodies parallel to the fiber orientation direction, and the number of measurements was n=5, and the average value was taken as the tensile strength. The measurement device used was an "Instron (registered trademark)" 5565 type universal material testing machine (manufactured by Instron Japan Co., Ltd.).

[0074] (5) Handling The prepreg was evaluated comprehensively based on the warp of the prepreg obtained, the tack of the prepreg surface, and the ease of unwinding of the rolled prepreg. Regarding the amount of warp, a rolled prepreg with a warp of 10 mm or less was evaluated as good. Regarding the tackiness of the prepreg surface, a tack tester (PICMA Tack Tester II: manufactured by Toyo Seiki Co., Ltd.) was used to press a cover glass of 18 mm x 18 mm onto the surface of the thermosetting resin layer of the composite prepreg with a force of 3.9 N for 5 seconds, and then the cover glass was pulled at a speed of 30 mm / min. The resistance force at the time of peeling was measured as a tack value for n=5. Those with an average value of 3.0 N or more were evaluated as good. Regarding the ease of unwinding of the rolled prepreg, those that did not unwind due to cracks or warping of the prepreg when 100 m of the rolled prepreg were produced while being wound around a paper tube with a diameter of 300 mm were evaluated as good. A three-point relative evaluation was used: A was good in all respects, B was good with two or more points, and C was poor with two or more points.

[0075] (6) Amount of warping The composite prepregs produced in each Example and Comparative Example were cut into five pieces measuring 300 mm square. Each cut composite prepreg was press molded at 130°C for 2 hours at 0.6 MPa to obtain a molded product in which the thermosetting resin was cured. The molded product was placed on a horizontal plate, and the height (distance from the horizontal plate) of the fourth corner of the molded product was measured with three of the four corners of the molded product in contact with the horizontal plate, and the arithmetic average value of N=5 was taken as the amount of warpage.

[0076] (7) Roughness average height Rc and roughness average length RSm of the interface curve The composite prepregs produced in each Example and Comparative Example were press molded under conditions of 130°C, 2 hours, and 0.6 MPa to obtain molded bodies in which the thermosetting resin was cured. The molded bodies obtained were cut perpendicular to the planar direction, and an image of the observation cross section was taken at 1000x magnification using an optical microscope. In any observation area of ​​500 μm square in the obtained image, the roughness average length RSm and roughness average height Rc of the cross-sectional curve element obtained by the above-mentioned measurement method 1 for cross-sectional curve element, as defined in JIS B0601 (2001), were measured.

[0077] <Example> The materials used in the following Examples and Comparative Examples are as follows.

[0078] [Glass fiber] A continuous E-glass fiber with a total of 1,600 single yarns that have been bundled. The characteristics are as follows: Single fiber diameter: 13μm Tensile strength: 3400MPa Tensile modulus: 72GPa Tensile elongation: 3% Density: 2.6g / cm 3

[0079] [Glass fiber fabric] Made from the above E-glass fiber, 260g / m 2 A plain weave glass fiber fabric.

[0080] [Carbon fiber 1] A copolymer mainly composed of polyacrylonitrile was spun, calcined, and surface-oxidized to obtain continuous carbon fibers with a total of 12,000 single fibers. The properties of this continuous carbon fiber are as follows: Single fiber diameter: 7μm Density: 1.8g / cm 3 Strand tensile strength: 4600MPa Strand tensile modulus: 220GPa

[0081] [Carbon fiber 2-7] Carbon fibers 2 to 7 were obtained by obtaining a common carbon fiber bundle as a raw material by the following method, and then applying various sizing compounds to the bundle. That is, first, an acrylonitrile copolymer copolymerized with itaconic acid was spun and baked to obtain a fiber having a total filament count of 24,000 and a specific gravity of 1.8 g / cm. 3 A carbon fiber bundle having a strand tensile strength of 5.9 GPa and a strand tensile modulus of 294 GPa was obtained. Various sizing agent compounds were then mixed with acetone to obtain a solution of about 1 mass % in which the compounds were uniformly dissolved. Each compound was applied to the carbon fiber bundle by immersion, and then heat-treated at 210°C for 90 seconds, and the amount of each compound attached was adjusted to 0.5 parts by mass per 100 parts by mass of the carbon fiber to which each compound was attached. The sizing agent compounds used for each carbon fiber and the surface free energy after the sizing agent was applied are as follows: Carbon fiber 2: polyethylene glycol diglycidyl ether (Denacol (registered trademark) EX-841, manufactured by Nagase ChemteX Corporation), surface free energy 20 mJ / m 2 Carbon fiber 3: bisphenol A diglycidyl ether ("jER" (registered trademark) 828, manufactured by Mitsubishi Chemical Corporation), surface free energy 9 mJ / m 2 Carbon fiber 4: sorbitol polyglycidyl ether (Denacol (registered trademark) EX-614B, manufactured by Nagase ChemteX Corporation), surface free energy 32 mJ / m 2 Carbon fiber 5: Bisphenol A propylene oxide 24 mole adduct, surface free energy 18 mJ / m 2 Carbon fiber 6: Polyallylamine (PAA-01, Nippon Shokubai Co., Ltd.), surface free energy 32 mJ / m 2 Carbon fiber 7: Polyethyleneimine (SP-012, Nippon Shokubai Co., Ltd.), surface free energy 33 mJ / m 2

[0082] [Carbon fiber fabric] Carbon fiber fabric "TORAYCA" (registered trademark) C06343 (manufactured by Toray Industries, Inc.) was used. The properties of this fabric were as follows: Single fiber diameter: 7.0μm Weave: Plain weave Weight: 180g / m 2

[0083] [Carbon fiber mat] Carbon fiber 1 was cut to 5 mm with a cartridge cutter to obtain chopped carbon fiber. A dispersion liquid with a concentration of 0.1% by mass consisting of water and a surfactant (Polyoxyethylene lauryl ether (trade name) manufactured by Nacalai Tesques Co., Ltd.) was prepared, and a carbon fiber mat was produced from this dispersion liquid and chopped carbon fiber using a carbon fiber mat production device. The production device was equipped with a cylindrical container with a diameter of 1000 mm having an opening cock at the bottom of the container as a dispersion tank, and a linear transport part (inclined angle 30 °) connecting the dispersion tank and the papermaking tank. A stirrer was attached to the opening on the top surface of the dispersion tank, and chopped carbon fiber and dispersion liquid (dispersion medium) could be put in from the opening. The papermaking tank was a tank equipped with a mesh conveyor having a papermaking surface with a width of 500 mm at the bottom, and a conveyor capable of transporting a carbon fiber substrate (papermaking substrate) was connected to the mesh conveyor. Papermaking was performed with a carbon fiber concentration in the dispersion liquid of 0.05% by mass. The carbon fiber substrate was dried in a drying oven at 200°C for 30 minutes and trimmed to a desired width to obtain a carbon fiber mat. The basis weight of the obtained mat was 180 g / m 2 It was.

[0084] [Thermoplastic resin (PP-1)] A resin consisting of 100% by mass of unmodified polypropylene resin (Prime Polypro (registered trademark) J105G manufactured by Prime Polymer Co., Ltd.) was used. The melting point of this resin was about 160°C.

[0085] [Thermoplastic resin (PP-2)] A resin consisting of 80% by mass of unmodified polypropylene resin (Prime Polypro (registered trademark) J105G manufactured by Prime Polymer Co., Ltd.) and 20% by mass of acid-modified polypropylene resin (Admer (registered trademark) QB510 manufactured by Mitsui Chemicals, Inc.) was used. The melting point of this resin was approximately 160°C.

[0086] [Thermoplastic resin (PA)] The polyamide resin used was "Amilan" (registered trademark) CM1001 (manufactured by Toray Industries, Inc.) The melting point of this resin was approximately 215°C.

[0087] [Thermoplastic resin (PEKK)] The polyether ketone ketone resin "KEPSTAN" (registered trademark) 7002 (manufactured by Arkema Co., Ltd.) was used. The melting point of this resin was about 330°C.

[0088] [Thermosetting resin (EP)] Into a kneader, 50 parts by mass of bisphenol A type epoxy resin ("jER" (registered trademark) 825, manufactured by Mitsubishi Chemical Corporation) epoxy equivalent: 175 (g / eq.), 50 parts by mass of phenol novolac type epoxy resin ("jER" (registered trademark) 154, manufactured by Mitsubishi Chemical Corporation) epoxy equivalent: 178 (g / eq.), and 3 parts by mass of polyvinyl formal ("Vinylec" (registered trademark) K, manufactured by JNC Corporation) were charged, and the polyvinyl formal was dissolved by heating and kneading. Next, while continuing the kneading, the temperature was lowered to 100°C or less, and 5 parts by mass of dicyandiamide (DICY7, manufactured by Mitsubishi Chemical Corporation) and 2 parts by mass of toluenebis(dimethylurea) ("Omicure" (registered trademark) U-24M, manufactured by CVC Thermoset Specialties) were added and stirred to obtain an EP.

[0089] In the following Examples and Comparative Examples, the method for producing the prepregs before compounding is as follows.

[0090] [Production method I (prepreg production method)] A 300 mm-wide resin sheet is placed on each side of a 300 mm-wide continuous reinforcing fiber sheet made of reinforcing fibers pulled out from a creel, and the sheet is heat-rolled to impregnate the continuous reinforcing fiber sheet with the resin sheet made of thermoplastic resin or thermosetting resin while applying heat and pressure, leaving no areas unimpregnated with resin.

[0091] [Production method II (semipreg production method)] Two resin sheets made of thermoplastic resin and each having a width of 300 mm are superimposed on one side of a continuous reinforcing fiber sheet made of reinforcing fibers and having a width of 300 mm pulled out from a creel, and the resin sheet is impregnated into the continuous reinforcing fiber sheet while being heated and pressurized by a heat roll so that the surface opposite to the surface where the resin sheets are superimposed has a resin-unimpregnated region having a volume of 10% of the sum of the volumes of the continuous reinforcing fiber sheet and the resin sheet. In the compounding process described later, the resin-unimpregnated region is heated and pressed. hardening The resin layer is placed so as to be in contact with the resin layer.

[0092] [Production method III (how to create discontinuous prepreg)] A 300 mm wide resin sheet is placed on each side of a 300 mm wide carbon fiber mat sheet pulled out from a creel, and the sheet is heat rolled to impregnate the carbon fiber mat sheet with the thermosetting resin while applying heat and pressure, leaving no areas unimpregnated with resin.

[0093] (Example 1-1) A thermoplastic prepreg was produced by the above method (I) using carbon fiber fabric as the reinforcing fiber and PP-2 as the thermoplastic resin, and a thermosetting prepreg was produced by the above method (I) using glass fiber fabric as the reinforcing fiber and EP as the thermosetting resin. Then, the thermoplastic prepreg with a width of 300 mm and the thermosetting prepreg with a width of 300 mm were each unwound in a roll and heat-rolled at a temperature of the melting temperature of the thermoplastic resin + 20°C to combine the thermoplastic prepreg and the thermosetting prepreg while heating and pressurizing, thereby obtaining a composite prepreg.

[0094] (Example 1-2) A composite prepreg was obtained in the same manner as in Example 1-1, using a thermoplastic prepreg prepared by the above method (I) using unidirectionally aligned carbon fibers 1 as the reinforcing fibers and PP-2 as the thermoplastic resin, and a thermosetting prepreg prepared by the above method (I) using unidirectionally aligned glass fibers as the reinforcing fibers and EP as the thermosetting resin.

[0095] (Examples 1-3) A composite prepreg was obtained in the same manner as in Example 1-1 using a thermoplastic prepreg prepared by the above method (I) using carbon fibers 1 aligned in one direction as the reinforcing fibers and PP-2 as the thermoplastic resin, and a thermosetting prepreg prepared by the above method (I) using carbon fibers 1 aligned in one direction as the reinforcing fibers and EP as the thermosetting resin.

[0096] (Examples 1 to 4) A thermoplastic prepreg (semipreg) was produced by the above method (II) using carbon fiber 1 arranged in one direction as the reinforcing fiber and PEKK as the thermoplastic resin, and a thermosetting prepreg was produced by the above method (I) using carbon fiber 1 arranged in one direction as the reinforcing fiber and EP as the thermosetting resin. Then, a 300 mm wide thermoplastic prepreg and a 300 mm wide thermosetting prepreg were each unwound and arranged so that the resin-unimpregnated area of ​​the thermoplastic prepreg was in contact with the thermosetting prepreg. The thermoplastic prepreg and the thermosetting prepreg were combined at 130°C while being heated and pressurized so that the thermosetting resin was impregnated into the resin-unimpregnated area, and a composite prepreg was obtained.

[0097] (Examples 1 to 5) A composite prepreg was obtained in the same manner as in Examples 1-4, except that PA was used as the thermoplastic resin for the thermoplastic prepreg. The roughness average height Rc and roughness average length RSm of the interface curve in this composite prepreg (i.e., the molded product) were 21 μm and 63 μm, respectively.

[0098] (Examples 1 to 6) A composite prepreg was obtained in the same manner as in Example 1-4, except that PP-1 was used as the thermoplastic resin for the thermoplastic prepreg. The roughness average height Rc and roughness average length RSm of the interface curve in this composite prepreg (i.e., the molded product) were 38 μm and 55 μm, respectively.

[0099] (Examples 1 to 7) A thermoplastic prepreg was prepared by the above method (I) using carbon fiber 1 arranged in one direction as the reinforcing fiber and PP-2 as the thermoplastic resin, and a thermosetting prepreg was prepared by the above method (III) using carbon fiber mat as the reinforcing fiber and EP as the thermosetting resin. Then, a thermoplastic prepreg with a width of 300 mm and a thermosetting prepreg with a width of 300 mm were rolled out, and a heat roll was performed at a temperature of the melting temperature of the thermoplastic resin + 20 ° C., and the thermoplastic prepreg and the thermosetting prepreg were composited while heating and pressing to obtain a composite prepreg. Note that the adhesive strength was obtained up to the time before the thermosetting resin layer broke during the test. In addition, the roughness average height Rc and roughness average length RSm of the interface curve in this composite prepreg (i.e., the molded body) were 29 μm and 72 μm, respectively.

[0100] (Comparative Example 1-1) Using glass fiber fabric as the reinforcing fiber and PP-2 as the thermoplastic resin, a 300 mm wide thermoplastic prepreg prepared by the above method (II) and a 300 mm wide thermosetting resin sheet prepared from a thermosetting resin (EP) were each unwound and laminated so that the resin-unimpregnated area of ​​the thermoplastic prepreg was in contact with the thermosetting resin sheet. A heat roll was then performed at 130°C to combine the thermoplastic prepreg and the thermosetting resin sheet while heating and pressurizing, thereby obtaining a composite prepreg.

[0101] (Comparative Example 1-2) A composite prepreg was obtained in the same manner as in Example 1-1 using a thermoplastic prepreg prepared by the above method (I) using carbon fibers 1 arranged in one direction as reinforcing fibers and PA as a thermoplastic resin, and a thermosetting prepreg prepared by the above method (I) using carbon fibers 1 arranged in one direction as reinforcing fibers and EP as a thermosetting resin. The adhesive strength and the amount of warping could not be measured because the thermoplastic resin layer and the thermosetting resin layer peeled off when the sample was set. In addition, an attempt was made to measure the roughness average height Rc and roughness average length RSm of the interface curve in this composite prepreg (i.e., the molded body), but voids occurred in the thermoplastic resin layer and the thermosetting resin layer due to the decomposition of the thermosetting resin, and Rc and RSm could not be measured.

[0102] (Comparative Example 1-3) A composite prepreg was obtained in the same manner as in Comparative Example 1-2, except that PP-1 was used as the thermoplastic resin of the thermoplastic prepreg. The adhesive strength and the amount of warping could not be measured because the thermoplastic resin layer and the thermosetting resin layer peeled off when the sample was set, and the thermoplastic resin layer and the thermosetting resin layer also peeled off in the tensile test of the molded product, so that the tensile strength of the molded product could not be measured. When the roughness average height Rc and the roughness average length RSm of the interface curve in this composite prepreg (i.e., the molded product) were measured, they were 0 μm and 55 μm, respectively.

[0103] (Example 2-1) A composite prepreg was obtained in the same manner as in Example 1-1 using a thermoplastic prepreg prepared by the above method (I) using carbon fibers 3 aligned in one direction as the reinforcing fibers and PP-2 as the thermoplastic resin, and a thermosetting prepreg prepared by the above method (I) using carbon fibers 3 aligned in one direction as the reinforcing fibers and EP as the thermosetting resin.

[0104] (Example 2-2) A composite prepreg was obtained in the same manner as in Example 2-1, except that carbon fiber 4 was used as the reinforcing fiber of the thermoplastic prepreg.

[0105] (Example 2-3) A composite prepreg was obtained in the same manner as in Example 2-1, except that carbon fiber 2 was used as the reinforcing fiber of the thermoplastic prepreg.

[0106] (Examples 2-4) A composite prepreg was obtained in the same manner as in Example 2-1, except that carbon fiber 5 was used as the reinforcing fiber of the thermoplastic prepreg.

[0107] (Examples 2-5) A composite prepreg was obtained in the same manner as in Example 2-1, except that carbon fiber 6 was used as the reinforcing fiber of the thermoplastic prepreg.

[0108] (Examples 2-6) A composite prepreg was obtained in the same manner as in Example 2-1, except that carbon fiber 7 was used as the reinforcing fiber of the thermoplastic prepreg.

[0109] (Examples 2-7) A composite prepreg was obtained in the same manner as in Example 2-1, except that carbon fiber 5 was used as the reinforcing fiber of the thermoplastic prepreg and carbon fiber 4 was used as the reinforcing fiber of the thermosetting prepreg.

[0110] (Examples 2-8) A composite prepreg was obtained in the same manner as in Example 2-1, except that carbon fiber 5 was used as the reinforcing fiber of the thermoplastic prepreg and carbon fiber 2 was used as the reinforcing fiber of the thermosetting prepreg.

[0111] <Consideration> A comparison of Examples 1-1 to 1-7 and Comparative Examples 1-1 to 1-3 showed that a prepreg having excellent adhesive strength between the thermoplastic resin layer and the thermosetting resin layer and good fiber dispersion has excellent mechanical properties and is also effective in terms of handleability.

[0112] In Example 1-1, it was shown that the method can be applied even when the reinforcing fibers are woven. In Example 1-2, it was revealed that the tensile strength of the molded body was improved by using unidirectionally oriented reinforcing fibers, and it was also shown that the method can be applied even when the types of reinforcing fibers contained in the thermoplastic resin layer and the thermosetting resin layer are different. Furthermore, a comparison between Example 1-2 and Example 1-3 showed that the mechanical properties were improved by aligning the reinforcing fibers with carbon fibers, and the difference in linear expansion coefficient between the thermoplastic resin layer and the thermosetting resin layer was reduced, thereby reducing warping and improving handling. In addition, in a comparison between Examples 1-4, 1-5, and Comparative Example 1-2, when a thermoplastic resin having a melting point higher than about 180°C, which is the upper limit of the process temperature range of the thermosetting resin, such as PEKK or PA, is used, if it is heated for a long time at or above the melting point of the thermoplastic resin to integrate it, the thermosetting resin in Comparative Example 1-2, in which the thermoplastic prepreg is obtained by the method [I], undergoes a decomposition reaction, and the adhesive strength is significantly reduced. The prepreg obtained in this case not only has poor mechanical properties, but also has poor handling properties, as the thermoplastic resin layer and the thermosetting resin layer peel off easily. However, it was shown that a prepreg in which the thermoplastic resin layer and the thermosetting resin layer are firmly bonded can be obtained by applying a manufacturing method in which the thermoplastic prepreg is made into a semipreg as in Examples 1-4 and 1-5. Furthermore, in the comparison between Examples 1-6 and Comparative Example 1-3, it was shown that a composite prepreg can be obtained by making the thermoplastic prepreg into a semipreg and impregnating the resin-unimpregnated part of the semipreg with a thermosetting resin, even if the unmodified polypropylene has low adhesion to the epoxy resin.

[0113] In Examples 2-1 to 2-8, the greater the surface free energy of the reinforcing fibers of the thermoplastic prepreg, the greater the improvement in adhesive strength, and the selection of a sizing agent improved fiber variation. Furthermore, the improvement in fiber variation reduced warping of the composite prepreg. It was also found that the adhesive strength could be further improved by increasing the surface free energy of the reinforcing fibers of the thermosetting prepreg.

[0114] [Table 1]

[0115] [Table 2] [Industrial Applicability]

[0116] The composite prepreg and fiber-reinforced composite material of the present invention are preferably used for aircraft structural members, wind turbine blades, automobile exterior panels, computer applications such as IC trays and notebook computer casings, and sports applications such as golf shafts and tennis rackets. [Explanation of symbols]

[0117] 1: Composite prepreg or fiber reinforced resin molding 2: Reinforced fiber 3: Thermoplastic or thermosetting resin 4: Orientation direction of any reinforcing fiber 5: Observation cross section 6: Cross-sectional image 7: Reinforced fiber 8: Thermoplastic resin layer 9: Thermosetting resin layer 10: Interface 11: Reference line 12: Orthobase line 13: Interface curve 14: Cross-sectional image 15: Prepreg surface 16: Thickness of thermoplastic resin layer 17: Another thermoplastic resin layer 18: Thickness of thermosetting resin layer

Claims

1. A composite prepreg in which a thermoplastic resin and a thermosetting resin are impregnated into reinforcing fibers, and a thermoplastic resin layer and a thermosetting resin layer are formed and bonded to each other by forming an interface, A thermoplastic resin layer is present on at least one surface, and the thermoplastic resin layer contains continuous reinforcing fibers; In a cross section perpendicular to the plane direction, reinforcing fibers are distributed in an area of ​​80% or more of the thickness of each of the thermoplastic resin layer and the thermosetting resin layer, and the adhesive strength between the thermoplastic resin layer and the thermosetting resin layer is 1 N / 24 mm or more.

2. The composite prepreg according to claim 1, wherein a volume content of the reinforcing fibers in the thermoplastic resin layer is 10% or more.

3. 3. The composite prepreg according to claim 1 or 2, wherein the coefficient of variation Q of the fiber content of the reinforcing fiber per unit section of 0.05 mm square in the thermoplastic resin layer is 40% or less.

4. The composite prepreg according to any one of claims 1 to 3, wherein the reinforcing fibers are carbon fibers.

5. The composite prepreg according to any one of claims 1 to 4, wherein the thermosetting resin layer contains continuous reinforcing fibers.

6. The reinforcing fibers contained in the thermoplastic resin layer have a surface free energy measured by the Wilhelmy method of 10 to 50 mJ / m 2 The composite prepreg according to any one of claims 1 to 5, wherein the reinforcing fibers are

7. The composite prepreg according to any one of claims 1 to 6, wherein in the thermoplastic resin layer and the thermosetting resin layer, reinforcing fibers oriented in one direction are arranged in one layer or multiple layers.

8. The composite prepreg according to any one of claims 1 to 7, wherein the reinforcing fibers contained in the thermoplastic resin layer and the thermosetting resin layer are the same.

9. When a cross section is observed that is at an angle of 45 degrees with respect to the orientation direction of the continuous reinforcing fibers and perpendicular to the plane direction of the prepreg, the cross section is formed by the interface between the thermosetting resin layer and the thermoplastic resin layer. The composite prepreg according to any one of claims 1 to 8, wherein the roughness average length RSm defined in JIS B0601 (2013) is 100 μm or less and the roughness average height Rc is 3.5 μm or more.

10. A method for producing a composite prepreg, comprising stacking a thermoplastic semipreg, in which continuous reinforcing fibers are impregnated with a thermoplastic resin while leaving unimpregnated areas on the surface, and a thermosetting prepreg, in which reinforcing fibers are impregnated with a thermosetting resin, so that the thermoplastic semipreg is in contact with the unimpregnated areas, and then heating and pressing the stacked prepreg.

11. A method for manufacturing a composite prepreg as described in Claim 10, wherein the thermoplastic semipreg has an impregnation rate of thermoplastic resin of 50% or more.

Citation Information

Patent Citations

  • Carbon fiber reinforced resin molded product and its manufacture

    JP1998138354A

  • Fiber-reinforced composite material, its production method and integrally structured material using it

    JP2006044261A

  • High-functionality composite

    JP2007283758A

  • Prepreg, method for manufacturing prepreg, and carbon fiber-reinforced composite material

    JP2014145038A

  • Sizing agent applied carbon fiber, manufacturing method of sizing agent applied carbon fiber, and prepreg and carbon fiber reinforced thermoplastic resin composition

    JP2014152403A